2007
DOI: 10.1093/schbul/sbm114
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavior Therapy for Schizophrenia: Effect Sizes, Clinical Models, and Methodological Rigor

Abstract: Background: Guidance in the United States and United Kingdom has included cognitive behavior therapy for psychosis (CBTp) as a preferred therapy. But recent advances have widened the CBTp targets to other symptoms and have different methods of provision, eg, in groups. Aim: To explore the effect sizes of current CBTp trials including targeted and nontargeted symptoms, modes of action, and effect of methodological rigor. Method: Thirty-four CBTp trials with data in the public domain were used as source data for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

39
740
5
40

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 919 publications
(824 citation statements)
references
References 98 publications
39
740
5
40
Order By: Relevance
“…In the ACT arm of the current study, a significant association was found between changes in depression and changes in mindfulness skills. To date methodologically rigorous research has failed to evidence the effectiveness of CBTp for treating depression in psychosis (Wykes et al, 2008). This is all the more concerning in light of Saarni et al's (2010) finding that depressive symptoms are the strongest predictors of poor quality of life in psychotic disorders.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…In the ACT arm of the current study, a significant association was found between changes in depression and changes in mindfulness skills. To date methodologically rigorous research has failed to evidence the effectiveness of CBTp for treating depression in psychosis (Wykes et al, 2008). This is all the more concerning in light of Saarni et al's (2010) finding that depressive symptoms are the strongest predictors of poor quality of life in psychotic disorders.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Randomised clinical trials have found that Cognitive Behaviour Therapy for psychosis (CBTp) is efficacious for treating residual distressing positive and negative symptoms (Wykes et al, 2008). However, the evidence for treating emotional dysfunction (such as anxiety, depression and hopelessness) is less clear (Birchwood, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 35 CBT clinical trials (9) recently showed that, although the vast majority of studies focused on positive symptoms as the primary treatment target, CBT also had beneficial impact on functioning. Fifteen of the studies reviewed included functioning measures and the average effect size for improvement in functioning ( d =0.38) and negative symptoms ( d =0.44) was comparable to that for positive symptoms ( d =0.37).…”
mentioning
confidence: 99%
“…P. Morrison et al 2011;Rathod et al 2008;Tarrier et al 2004). Certain psychosocial treatments, such as cognitive behaviour therapy (CBT) , have been shown to have a beneficial effect on positive and negative symptoms, mood, social functioning and social anxiety and is effective in reducing readmissions to hospital, duration of admission and symptom severity (Lysaker et al 2010), (Wykes et al 2008). CBT therefore addresses the limitations of medication- (Kreyenbuhl et al 2010).…”
Section: Introductionmentioning
confidence: 99%